SUMO-1 and p53 - Melchior, Frauke; Hengst, Ludger (Cell cycle, 2002)
Abundance and activity of the tumor suppressor p53 are regulated by many different posttranslational modifications. These include phosphorylation, acetylation, ribosylation, O-glycosylation or ubiquitination. Three years ago, covalent modification with the ubiquitin- related protein SUMO-1 has been added to this list. SUMO-1 resembles ubiquitin both in structure and in the mechanism of attachment, and is reversibly attached to a large number of proteins. Molecular consequences of this dynamic modification vary between targets and include alterations in protein/protein or protein/DNA interactions, changes in localization, enzymatic activity, or stability. A role of SUMOylation in modulating p53 transcriptional activity has been reported, but is still an issue of controversy. Here we will briefly summarize the pathway of SUMOylation and discuss possible implications for p53 function.
Gesehen am 17.08.2023